2020
DOI: 10.1002/esp.4781
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of landslides in forests and grasslands triggered by the 2016 Kumamoto earthquake

Abstract: We examined the characteristics of landslides triggered by the 2016 Kumamoto earthquake (Mw = 7.0: focal depth=10.0 km) in forests and grasslands within two affected watersheds (Tokosegawa: 6.9 km2 and Nigorigawa: 6.1 km2) in southwestern Japan. We identified 190 landslides using aerial photographs and analyzed their sizes by geographic information system (GIS). Field investigations were conducted to obtain landslide depth, volume and residual sediment for 38 selected landslides (21 in forests and 17 in grassl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 58 publications
2
16
1
Order By: Relevance
“…[2018] showed that more than 50% of 13,097 landslides in the 2015 Mw 7.8 Gorkha earthquake in Nepal had areas ranging from 10 3 to 10 6 m 2 . These landslides occurred in areas of high relief, but the sizes of the landslides of our study were similar to the landslides reported by Koyanagi et al . [2020] in the 2016 Mw 7.0 Kumamoto earthquake, Japan (range : 34-8835 m 2 ; mean : 1511 m 2 ), possibly because of similar local relief.…”
Section: Characteristics Of Landslidessupporting
confidence: 91%
See 4 more Smart Citations
“…[2018] showed that more than 50% of 13,097 landslides in the 2015 Mw 7.8 Gorkha earthquake in Nepal had areas ranging from 10 3 to 10 6 m 2 . These landslides occurred in areas of high relief, but the sizes of the landslides of our study were similar to the landslides reported by Koyanagi et al . [2020] in the 2016 Mw 7.0 Kumamoto earthquake, Japan (range : 34-8835 m 2 ; mean : 1511 m 2 ), possibly because of similar local relief.…”
Section: Characteristics Of Landslidessupporting
confidence: 91%
“…The landslide density observed in our study area, 48 landslides/km 2 , was higher than that reported in previous studies. For example, Koyanagi et al . [2020] showed that the landslide density in the 6.9 km 2 Tokosegawa watershed in Kumamoto was 12.4 landslides/km 2 .…”
Section: Characteristics Of Landslidesmentioning
confidence: 99%
See 3 more Smart Citations